2012
DOI: 10.1590/s1806-37132012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento da hiperinsuflação dinâmica em teste em esteira rolante em pacientes com DPOC moderada a grave

Abstract: Objective: To characterize the presence, extent, and patterns of dynamic hyperinflation (DH) during treadmill exercise testing in patients with moderate to severe COPD. Methods: This was a cross-sectional study involving 30 non-hypoxemic patients (FEV 1 = 43 ± 14% of predicted) who were submitted to a cardiopulmonary exercise test on a treadmill at a constant speed (70-80% of maximum speed) to the tolerance limit (Tlim). Serial inspiratory capacity (IC) maneuvers were used in order to assess DH. Results: Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…( 22 - 25 ) In contrast, Guenette et al ( 26 ) recently analyzed a total of 130 COPD patients (whose FEV1 values were similar to those observed in previous studies, i.e., ~ 40-50% of predicted) and reported that the presence or absence of DH during exercise had no influence on the intensity of dyspnea or on exercise tolerance during high-intensity exercise. On the contrary, critical restriction of tidal volume expansion was shown to be the primary mechanism associated with those outcomes, independently of the presence of DH.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…( 22 - 25 ) In contrast, Guenette et al ( 26 ) recently analyzed a total of 130 COPD patients (whose FEV1 values were similar to those observed in previous studies, i.e., ~ 40-50% of predicted) and reported that the presence or absence of DH during exercise had no influence on the intensity of dyspnea or on exercise tolerance during high-intensity exercise. On the contrary, critical restriction of tidal volume expansion was shown to be the primary mechanism associated with those outcomes, independently of the presence of DH.…”
Section: Discussionmentioning
confidence: 83%
“…( 22 - 25 ) Por outro lado, mais recentemente, Guenette et al, ( 26 ) analisando um total de 130 pacientes com DPOC (na mesma faixa aproximada de gravidade do VEF 1 dos estudos anteriores, ou seja, ~ 40-50% do previsto), descreveram que a presença ou a ausência de HD no exercício não influenciou a intensidade da dispneia ou a tolerância durante exercício de alta intensidade. Pelo contrário, foi demonstrado que a limitação crítica na expansão do volume corrente foi o principal mecanismo associado com esses desfechos, independentemente da presença de HD.…”
Section: Discussionunclassified
“…The authors also observed greater impairment of resting lung function in patients with DH than in those without DH. 32 In another Brazilian study, a randomized work including 30 COPD volunteers without severe hypoxemia, Scuarcialupi et al found that improvement in resting IC after bronchodilator use was associated with increased tolerance to effort, even in patients with COPD without DH. However, patients who showed no increase in resting IC were still able to obtain a functional benefit from bronchodilator use, provided they presented with DH during exercise.…”
Section: Resultsmentioning
confidence: 98%
“…Cordoni et al 19 also found increased dyspnea score after stress test and attributed this condition to the movement of the arms, which causes the intercostal inspiratory muscles contribute less to respiratory mechanics, because they are actively participating in the support of the arms and trunk. The abdominal muscles also aid in stabilizing the trunk, being less efficient in expiratory lung emptying and, as a result, less efficient gas exchange and a worsening of ventilation/perfusion mismatching.…”
Section: Discussionmentioning
confidence: 98%